2023
DOI: 10.1002/tox.23794
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctane sulfonate‐induced apoptosis in kidney cells by triggering the NOX4/ROS/JNK axis and antagonism of cannabidiol

Abstract: Perfluorooctane sulfonate (PFOS) is one of the persistent organic pollutants (POPs), which can cause severe nephrotoxicity in mammals. Cannabinol (CBD), a nonpsychoactive cannabinoid obtained from the cannabis plant, has attracted attention in recent years for its excellent antioxidant properties. NADPH oxidase 4 (NOX4) has an important effect in supporting normal renal physiological function. The potential mechanisms of PFOS nephrotoxicity and whether CBD can prevent renal damage caused by PFOS remain unclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 51 publications
(123 reference statements)
1
6
0
Order By: Relevance
“…Numerous studies have shown that tissue and organ damage due to selenium deficiency is closely related to oxidative stress. 52 In the present study, we found that the levels of CAT, SOD and GSH decreased while MDA, H 2 O 2 , TNOS and iNOS activities increased in chicken liver tissue and LMH cells after selenium deficiency. In addition, knockdown of SelM and overexpression of miR-138-5p increased the level of intracellular ROS, which was alleviated by NAC addition.…”
Section: Discussionsupporting
confidence: 55%
“…Numerous studies have shown that tissue and organ damage due to selenium deficiency is closely related to oxidative stress. 52 In the present study, we found that the levels of CAT, SOD and GSH decreased while MDA, H 2 O 2 , TNOS and iNOS activities increased in chicken liver tissue and LMH cells after selenium deficiency. In addition, knockdown of SelM and overexpression of miR-138-5p increased the level of intracellular ROS, which was alleviated by NAC addition.…”
Section: Discussionsupporting
confidence: 55%
“…The results of a study suggest that treatment with Δ -9-THC reduced kidney injury caused by ischemia-reperfusion injury and inflammation through the reducing oxidative stress in the kidney tissue [26]. In addition, Several studies have found that the ECS has a role in renal inflammation, oxidative stress, and fibrosis, which are key factors in nephrotoxicity development and progression [25,[27][28][29]. While the exact protective mechanisms of cannabinoids such as CBD, THC, as well as endocannabinoids against nephrotoxicity are not completely understood, it is believed that they produce this effect through various pathways that include promoting the regeneration of damaged cells in addition to the reduction of apoptosis, inflammation, and oxidative stress [28,29].…”
Section: The Potential Role Of Cannabinoids As a Protective Agent Aga...mentioning
confidence: 99%
“…In addition, Several studies have found that the ECS has a role in renal inflammation, oxidative stress, and fibrosis, which are key factors in nephrotoxicity development and progression [25,[27][28][29]. While the exact protective mechanisms of cannabinoids such as CBD, THC, as well as endocannabinoids against nephrotoxicity are not completely understood, it is believed that they produce this effect through various pathways that include promoting the regeneration of damaged cells in addition to the reduction of apoptosis, inflammation, and oxidative stress [28,29]. Inflammation is one of the major factors contributing to renal disease, and various studies show that cannabinoids have anti-inflammatory effects.…”
Section: The Potential Role Of Cannabinoids As a Protective Agent Aga...mentioning
confidence: 99%
“…Oxidative stress can lead to damages in the body. The ROS‐driven JNK signaling pathway was responsible for the induction of kidney apoptosis by Perfluorooctane sulfonate (Du et al, 2023). A study investigates lead‐induced kidney inflammation through ROS‐mediated MAPKs and NF‐κB pathway (Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%